Promoting proactive auditing behaviors - Peecher, Mark E.; Ricci, Michael A.; Zhou, Yuepin (Daniel) (Contemporary Accounting Research, 2024)
Abstract In this paper, we introduce the construct of proactive auditing behaviors to the accounting literature and report the first experimental investigation of their antecedents. Regulators and practitioners agree that proactive behaviors are needed to consistently achieve high‐quality audit outcomes, but also that these behaviors are scarce. Drawing on theory from management, accounting, and psychology, we predict that an environmental factor (autonomy) and a dispositional factor (tacit knowledge) interact to increase a range of distinct proactive auditing behaviors. These behaviors involve responding to evidence that has out‐of‐task implications, coordinating with clients to acquire task‐related evidence, and two forms of coaching junior auditors. As predicted, we find that auditors are more proactive when they have both higher autonomy and higher tacit knowledge than when they lack either or both factors. Our theory and findings inform academics, regulators, and practitioners about the types of work environments and policies that can promote auditor proactivity successfully.